Women on Corporate Boards in Bosnia and Herzegovina, FYR Macedonia, and Serbia - Djulic, Katarina; Kuzman, Tanja (International Finance Corporation, Washington, DC, 2017)
In January 2013, International Finance Corporation (IFC) launched a research project entitled women on corporate boards in Bosnia and Herzegovina, FYR Macedonia, and Serbia. The purpose of the project was to gather information on the representation of women on corporate boards and to learn about the determinants of female board membership in these countries. Which skills and knowledge do women need to possess to become a member of a board? Do women’s decision-making and leadership styles differ from those of their male counterparts? Are there are any impediments for women aspiring to board membership? And what useful lessons can be learned to inform policy? The research was carried out over a period of four months. It started with desktop research conducted over a two-week period between January 21 and February 3, 2013 and which aimed at identifying around 30 female and male board members in each country covered by the project who were willing to participate. Interviews with board members were conducted between February 5 and March 23, 2013. The report presents research results. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.